Socialization of Bullying Prevention Through Storytelling Method for Elementary School Students at Private Islamic Elementary Schools - Nurul Setiani; Sulthaanika Ferdy Syahwardi; Budi Setiawan; Suryo Sulistyo; Marvinda Rizki Dita Dirgantara; Uswah Uswah; Faisal Kemal; Dyah Nursari A; Suci Nurazizah; Dilla Ayudya; Ferdiansyah Ardana; Devin Ramadhan; Nur Riza Dewi (UrbanGreen Central Media, 2026)
Bullying is one of the problems often experienced by elementary school students and can negatively affect children’s psychological, social, and academic development. Therefore, preventive efforts are needed through educational activities that are interesting and easily understood by children. This community service activity aimed to increase students’ understanding of bullying prevention through the storytelling method at a Private Islamic Elementary School. The activity was carried out using socialization, storytelling sessions, interactive discussions, and question-and-answer methods involving elementary school students as participants. The storytelling method was chosen because it is able to convey moral values in an engaging, enjoyable, and age-appropriate way for children. The results of the activity showed that students became more aware of the forms of bullying, the impacts caused by bullying behavior, and the importance of respecting and helping one another. Students also demonstrated enthusiasm and active participation during the activity. In conclusion, the storytelling method can be an effective educational medium in bullying prevention efforts among elementary school students because it helps students understand moral messages more easily and fosters positive character development from an early age.